Internet banking: a study of customer adoption and its effectiveness in Bank Islam Malaysia Berhad Kuching / Hasbullah Haji Sharkawi and Azman Mahli - Haji Sharkawi, Hasbullah; Mahli, Azman (2009)
Banking is a highly information intensive activity that relies heavily on information technology (IT) to acquire, process, and deliver the information to all relevant customers. Banks used the Internet technology as a strategic weapon to revolutionize the way they operate, deliver, and compete against each other. As a result Internet Banking was introduced as a channel where bank customers could perform their financial transactions electronically via their bank’s websites.